Schizo-obsessive disorder - case study - Kozłowska, Martyna; Iwanicka, Karolina; Idzik, Zuzanna; Ziemecki, Piotr (Current Problems of Psychiatry, 2022)
Introduction. Schizo-obsessive disorder is a term that includes a dual diagnosis: schizophrenia and obsessive-compulsive disorder (OCD). The schizo-obsessive disorder definition was made at the end of the 19th century and is still valid today. Nowadays, the coexistence of schizophrenia with obsessive-compulsive syndromes becomes more commonly observed, therefore the recognition and number of the described cases has increased.Material and methods. The aim of this article is to present a clinical case of a patient with a diagnostically and therapeutically difficult disorder, including the comorbidity of schizophrenia and OCD. The analysis of the clinical case and the medical records of a patient and a review of the literature including schizophrenia, OCD, and schizo-obsessive disorder, was performed.Case study. A male patient, 20 years old, single, high school student, who lives with his family. In November 2019 a mental deterioration occurred. Simultaneously, obsessional ideas and behaviors appeared. An ambulatory treatment was introduced, however without adequate response, which was the cause of the first psychiatric hospitalization in 2020.Discussion. Comorbidity between obsessive-compulsive disorder and schizophrenia may cause a particular problem for physicians. Without appropriate diagnosis, there is no possibility to implement proper management and treatment. Obsessivecompulsive symptoms should be treated as relatively common in patients with schizophrenia, which will prevent a mistake in the assessment of the patient's condition.Conclusions. Due to specific character of the disease, difficulties in diagnosis and treatment, there is a special need for individual therapeutic measures. Appropriate and targeted approach to the patient may be a chance for success in therapy.